Deskripsi Pertumbuhan dan Produksi Bibit Kentang (Solanum tuberosum L.) Varietas Granola dari Kultur Jaringan (Planlet) dan Stek Mini, Studi Kasus Taruna Bina Tani - Hutauruk, Sixtus; Tarigan, Rio Stepanus (AGROSUSTAIN, 2023)
This research aims to describe the production of Granola Variety potato seeds from tissue culture (plantlets) and mini cuttings in the Taruna Bina Tani green house in Bukit Village, Dolat Rakyat District, Karo Regency. The observation technique is carried out by direct observation and running a questionnaire. Mini cuttings plants sourced from plantlets will have the same genetic characteristics as their parents, meaning that even though the shoot stem cuttings are small, the results of propagation using the mini shoot cuttings system are also the same as plants originating from tissue culture seeds (parent seeds). Toruna Bina Tani is one of the producers of virus-free Granola Variety potato seeds in Tanah Karo. This business started in 2018. The breeding screen house covers an area of 5000 meters which actively produces generation 0 (G0) to generation 2 (G2) potato seeds which are distributed to farmers.The results showed that the growth of plantlets and mini cuttings was not different, the production of the number of plantlet tubers was greater than the production of the number of tubers of mini cuttings, on the other hand, the weight of tubers per plant, the weight of tubers per tuber and the weight of tubers per rack were smaller in plantlets than in mini cuttings. . Propagation via mini cuttings taken from plantlets is very effective in accelerating the fulfillment of quality seeds (G0). Each individual plantlet can produce 83.8 mini cuttings.